Dra‘ Abu el-Naga, Ägypten. Ein angeblicher Fund aus Dra‘ Abu el-Naga: Die sog. Hundestele des Königs Wah-Anch Intef – Eine Forschungsgeschichte - Polz, Daniel (e-Forschungsberichte des DAI, 2020)
The monument of the Eleventh Dynasty Theban ruler Horus Wah-Ankh Intef Aa (‘Intef II’) known as the ‘dog stela’ has been the subject of Egyptological investigations many times since its discovery in the middle of the 19th century, and has been discussed from many different perspectives. According to Egyptological tradition, the stela was discovered by the founding director of the Egyptian Antiquities Organization, Auguste Mariette, in the vast necropolis of Dra‘ Abu el-Naga (Western Thebes/Luxor) in 1860. A recent comprehensive study, however, reveals that neither of these points are correct: The stela was discovered by Mariette‘s first assistant, Marius F. J. Bonnefoy, in 1858, and not in Dra‘ Abu el-Naga but in the adjacent cemetery of el-Târif, today the name of a village further east. Although Mariette published a first drawing of the stela in 1872, it seems highly likely that he himself never actually saw the stela.